FORMATION OF A CULTURE OF HEALTHY LIFESTYLE IN THE FAMILY - Hoshimova Mohira Askhad kizi (Galaxy International Interdisciplinary Research Journal, 2021)
This article discusses the role of thinkers in shaping a healthy lifestyle in adolescent, the views of thinkers on family relationships, and the role of the family in shaping a healthy lifestyle culture in adolescents. Forming a culture of a healthy lifestyle for children. The question of the participation of parents in the formation of a culture of a healthy lifestyle in children of senior preschool age. The analysis of the health index dynamics of children, teenagers and young people of Russia during the last two decades testifies that there is a lasting tendency of decline of physical, mental and moral health of those under teaching. The social negative phenomena like tobacco-smoking, beer drinking and risky sexual behavior have become widely spread. The absence of continual system of pedagogical education focused on health value and healthy lifestyle is one of the major reasons of low efficiency of the work carried out by educational institutions. The article substantiates the potential possibilities of a foreign language as an aspect to provide those trained with continual formation of a healthy lifestyle and examines the work done within the frame of curriculum and extra-curriculum activities united by one topic.